Electronic cigarette use and consumption patterns in medical university students - Asli Gorek Dilektasli; Ozge Aydin Guclu; Arzu Ozpehlivan; Vahide Aslihan Durak; Izzet Gezmis; Anıl Ozgur; Burak Cinar; Ezgi Demirdogen; Nilufer Aylin Acet Ozturk; Guven Ozkaya; Funda Coskun; Ahmet Ursavas; et al. (Frontiers Media S.A., 2024)
BackgroundA major public health hazard is youth e-cigarette use. Although new, e-cigarette health hazards are becoming well-known in the literature. E-cigarette sale restrictions and laws differ globally. In this cross-sectional study, we studied medical university students' tobacco and e-cigarette use and characteristics in a country where sales and import of e-cigarettes are banned. The primary objective is to determine the prevalence of electronic cigarette use and understand consumption patterns among medical faculty students in this setting.Materials and methodsThe questionnaire was sent using a web-based student information system. Sociodemographic features, tobacco and e-cigarette use, consumption patterns, and e-cigarette risk perceptions were covered in 54 questions.ResultsThe study comprised 1,054 students (48.7% male) aged 21.5 ± 2.6 years who completed the questionnaire. 37.7%, 20.9% and 23.6% have smoked cigarettes, e-cigarettes, or water pipes. Current cigarette smokers were 17.0%, e-cigarette users 4.0%, and water pipe smokers 4.5%. E-cigarette users were 52.3% dual smokers. The most common symptoms reported by e-cigarette users were cough (58.4%) and dyspnea (54.2%). Multivariable models showed that the male sex, greater monthly income, and a current smoker friend were independent risk factors for e-cigarette ever use, while the male sex, paternal current smoking, and close friends' current smoking status were risk factors for dual use among medical trainees. Many medical students who used electronic cigarettes underestimated nicotine's health hazards and harmful chemicals in e-cigarettes. Despite e-cigarette sales being prohibited in our country, 56.4% and 25.4% of e-cigarette users provided e-cigarettes from tobacco shops and through online sales, respectively.ConclusionMedical university students use tobacco most often by smoking cigarettes. Despite medical university students being aware of the health hazards of e-cigarettes, the current use of electronic cigarettes is 4.0%. Male sex, greater monthly income, and having current smoker friends are independent risk factors for e-cigarette use, while paternal smoking is a risk factor for dual use among medical trainees. Although in the country, sales of e-cigarettes are banned, ever-use rates for e-cigarettes were remarkably high at 20.9%, and the ease of accessing e-cigarettes was striking.